The Influence of Teacher Creativity on Science Learning Outcomes of Islamic Elementary School - Alifia Putri, Nuris Salma; Shanie, Arsan (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research was quantitative research using field research methods carried out at MI Manbaul Ulum Sinoman Pati with the aim of finding out whether there was an influence of teacher creativity on student learning outcomes in science subjects at MI Manbaul Ulum Sinoman Pati. The population in this study was all class V students from both class A and class B, with a total of 38 students. From this population, samples were taken for this research using saturated sampling techniques or total sampling, where members of the entire population are members of the sample. The data used in this research consists of primary data and secondary data. Primary data was obtained through questionnaires distributed directly to class V students, while secondary data was in the form of literature that was relevant to research on teacher creativity and science learning outcomes. Data collection was carried out by means of questionnaires and documentation. The data analysis technique used is descriptive statistics and hypothesis testing using the t-test. The results of the hypothesis test show that it is known that the calculated t value is 8.231 with a significance level (2-tailed) of 0.000 with df = (n-k) = 38 -2 = 36 so that the t table is 1.688 at a significance level of 0.05. So, t count > t table or 8.231 > 1.688. So H0 is rejected, and Ha is accepted, so the meaning is that there is an influence of teacher creativity on student learning outcomes in science subjects at MI Manbaul Ulum Sinoman Pati.